A House in the Trees: The TowerHouse - Marlon Blackwell (Oz, 2003)
I live, practice, teach, and build in Northwest Arkansas, in the foothills of the Ozark Mountains. It’s a place considered to be in the middle of nowhere, yet ironically, close to everywhere.